Effect of dual endophyte inoculations on plant colonization, and control of Radopholus similis and the banana weevil - Paparu, P.; Dubois, T.; Coyne, Danny L.; Viljoen, Altus (2008)
The root burrowing nematode Radopholus similis and the banana weevil Cosmopolites sordidus are major pests of banana in the Lake Victoria basin region. An integrated pest management approach that includes habitat management, biological control, host plant resistance and chemical control is currently used to control populations of the two pests. Biological control strategies with potential to control the banana weevil and R. similis include the use of entomopathogenic fungi Beauveria bassiana and non-pathogenic Fusarium oxysporum endophytes of banana. The current study was designed to investigate the effect of dual endophyte inoculations on control of the two pests in ‘Nabusa’ ( spp., AAA-EA group). Endophytic F. oxysporum isolate V5w2 known to reduce R. similis numbers in screenhouse pot trials was inoculated together with isolate Emb2.4o, known to be effective against the banana weevil. Root and rhizome colonization was higher.